2019
DOI: 10.1186/s42358-019-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between dietary inflammatory index and low impact fractures in the Brazilian population: the Brazilian Osteoporosis Study (BRAZOS)

Abstract: Introduction: Adequate nutrition, including intake of dietary calcium and vitamin D, is important to maintain bone health. Evidence suggests that a deficiency in micronutrients may contribute to bone loss during aging and exert generalized effects on chronic inflammation. Recently, the Dietary Inflammatory Index (DII) was developed to assess the inflammatory potential of individual diets. Our aim was to evaluate the DII in a representative sample and verify its association with low-impact fractures. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
12
2
Order By: Relevance
“…Among the included studies, there were 8 high quality studies reporting the adjusted risk estimate for T2D associated with DII as the primary outcome [ 32 , 33 , 39 , 50 52 , 59 , 63 ], while for other studies [ 23 31 , 34 38 , 40 49 , 53 58 , 60 62 , 64 70 ], T2D was a secondary outcome and the crude odds ratio for T2D was calculated based on the frequency of subjects with T2D in the highest category of DII, compared with subjects in the lowest category. DII was calculated with the use of 7-day dietary record in 3 studies [ 31 , 44 , 50 ], 24-hour dietary recall in 11 studies [ 35 , 37 , 46 , 51 , 54 , 55 , 62 64 , 68 , 70 ], dietary history questionnaire in 2 studies [ 45 , 52 ], and food frequency questionnaire (FFQ) in the remaining studies. Moreover, data for men was reported in 7 studies [ 28 , 36 , 44 , 50 , 53 , 54 , 64 ] and for women was reported in 10 studies [ 24 , 28 , 34 , 36 , 38 , 49 , 52 , 54 , 64 , 67 ], and other studies reported results for a combination of both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, there were 8 high quality studies reporting the adjusted risk estimate for T2D associated with DII as the primary outcome [ 32 , 33 , 39 , 50 52 , 59 , 63 ], while for other studies [ 23 31 , 34 38 , 40 49 , 53 58 , 60 62 , 64 70 ], T2D was a secondary outcome and the crude odds ratio for T2D was calculated based on the frequency of subjects with T2D in the highest category of DII, compared with subjects in the lowest category. DII was calculated with the use of 7-day dietary record in 3 studies [ 31 , 44 , 50 ], 24-hour dietary recall in 11 studies [ 35 , 37 , 46 , 51 , 54 , 55 , 62 64 , 68 , 70 ], dietary history questionnaire in 2 studies [ 45 , 52 ], and food frequency questionnaire (FFQ) in the remaining studies. Moreover, data for men was reported in 7 studies [ 28 , 36 , 44 , 50 , 53 , 54 , 64 ] and for women was reported in 10 studies [ 24 , 28 , 34 , 36 , 38 , 49 , 52 , 54 , 64 , 67 ], and other studies reported results for a combination of both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Not all studies have reported positive associations between DII and bone health. The Brazilian Osteoporosis Study (n = 2269 adults ≥ 40 years old) failed to identify any link between DII scores and low-impact fractures [283]. In further work the relationship between DII scores and muscle mass and strength were examined in Chinese children (n = 466, age six–nine years).…”
Section: DII and Musculoskeletal Healthmentioning
confidence: 99%
“…In addition, in the study of the elderly population, pro-inflammatory foods were confirmed to increase the risk of fracture [ 46 ]. However in the Brazilian osteoporosis study, females had a higher DII score than males, but there was no association between DII score and fracture risk of vulnerability [ 47 ]. In our study, there was no association between DII and BMD.…”
Section: Discussionmentioning
confidence: 99%